If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y-y(y=1)
We move all terms to the left:
6y-y(y-(1))=0
We multiply parentheses
-y^2+6y+1y=0
We add all the numbers together, and all the variables
-1y^2+7y=0
a = -1; b = 7; c = 0;
Δ = b2-4ac
Δ = 72-4·(-1)·0
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{49}=7$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-7}{2*-1}=\frac{-14}{-2} =+7 $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+7}{2*-1}=\frac{0}{-2} =0 $
| 7/28=25*x | | b+1/2b+3=24 | | 16=5xx-8 | | -(x+15-7)=7 | | 5x-7=7x-(x-1)-1 | | 4^4x-10(4^2x)+16=0 | | 5x-10=+20 | | 0.9=0.3d | | 10-3a=18 | | x4+6x2+8=0 | | x4-6x2+8=0 | | 3y-y=-7+5 | | 2k^2+(-k)^2=180 | | 2/3=3-x | | 2x=32x | | 4x^2-30x+70=0 | | 2n+8=4~3 | | 8y-5=99 | | 9m-27=20 | | 8x+5=11x-4 | | 4f-7=9 | | 4x+6=-5x+9 | | 5x+1.5x^2-84=0 | | -6x+4=-2x | | 9×n=-117 | | 4(x-3)=2x-18 | | 4×s×6=48 | | 2x+30+1x+5=20+20 | | 36-x^2=48-8x | | 3n-6=7n-2 | | 16=m+71 | | 9x-63=5x+25 |